Prevalence of tooth wear and its associated risk factors among industrial workers in Daman, India: a cross-sectional study - Ahuja, Nikhil; Ahuja, Nirmal (International Journal Of Community Medicine And Public Health, 2017)
Background: Tooth wear is an ever increasing problem. Therefore, the aim of the present study was to assess the prevalence of tooth wear and its associated risk factors among industrial workers in Daman, India. Methods: This cross sectional study was conducted among 613 industrial workers selected using simple random sampling. The clinical assessment of tooth wear was done using tooth wear index (TWI) developed by Smith & Knight. A specifically designed questionnaire was used to seek information on risk factors of tooth wear. Data were analyzed using Pearson’s chi-square test, ANOVA and a multiple logistic regression model. Results: The overall prevalence of tooth wear was found to be greater in mandible (86.8%) as compared to maxilla (61.7%). In both maxilla and mandible, the most frequently affected teeth were incisors (55.8% and 83.7%) followed by canines (52.2% and 81.2%), pre molars (38.5% and 42.1%) and molars (37.8% and 38.8%). Among the risk factors, consumption of hard or acidic foods (p=0.01, OR=1.73) and use of hard toothbrush bristles (p=0.04, OR=0.04) in maxilla and clenching or grinding of teeth (p=0.01, OR=3.96) in mandible were significantly associated with tooth wear. However, work environment involving dust or acid gas was the only risk factor associated with tooth wear in both maxilla (p=0.004, OR=0.53) and mandible (p<0.001, OR=0.35). Conclusions: There is a high prevalence of tooth wear among industrial workers. Thus, efforts should be made by dentists to increase awareness about tooth wear and plan a three-level prevention program based on analysis of risk assessment.